Relationship of Self efficacy with Learning Motivation of Students of Class Phase F at SMA N1 Koto Salak, Dharmasraya Regency - Illahi, Rahmad; Kardo, Rici; Solina, Wira (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research is motivated by the existence of students who are not confident in increasing their learning motivation. In general, many students lack motivation to learn because they are not confident in their abilities. This research aims to determine: 1) students' self-efficacy, 2) students' learning motivation, 3) the relationship between self efficacy and students' learning motivation. This type of research is quantitative descriptive with a correlational approach. The population of this study was students in class Phase F at SMA N 1 Koto Salak, totaling 125 students. Sampling was carried out using the Slavin formula, the results of which were 96 students, and using a questionnaire as an instrument. The number of valid questionnaire statements after the trial was 70 statements for research. The results of this research show: 1) Students' self-efficacy is in the high category. 2) students' learning motivation is in the high category. There is a relationship between self-efficacy and students' learning motivation with a fairly strong coefficient.